Population dynamics of the Lyme disease bacterium, Borrelia burgdorferi , during rapid range expansion in New York State - Zachary J. Oppler; Melissa A. Prusinski; Kayleigh R. O'Keeffe; Patrick Pearson; Stephen M. Rich; Richard C. Falco; Vanessa Vinci; Collin O'Connor; Jamie Haight; P. Bryon Backenson; Dustin Brisson (Molecular Ecology, 2024)
Recent changes in climate and human land‐use have resulted in alterations of the geographic range of many species, including human pathogens. Geographic range expansion and population growth of human pathogens increase human disease risk. Relatively little empirical work has investigated the impact of range changes on within‐population variability, a contributor to both colonization success and adaptive potential, during the precise time in which populations are colonized. This is likely due to the difficulties of collecting appropriate natural samples during the dynamic phase of migration and colonization. We systematically collected blacklegged ticks ( Ixodes scapularis ) across New York State (NY), USA, between 2006 and 2019, a time period coinciding with a rapid range expansion of ticks and their associated pathogens including Borrelia burgdorferi , the etiological agent of Lyme disease. These samples provide a unique opportunity to investigate the population dynamics of human pathogens as they expand into novel territory. We observed that founder effects were short‐lived, as gene flow from long‐established populations brought almost all B. burgdorferi lineages to newly colonized populations within just a few years of colonization. By 7 years post‐colonization, B. burgdorferi lineage frequency distributions were indistinguishable from long‐established sites, indicating that local B. burgdorferi populations experience similar selective pressures despite geographic separation. The B. burgdorferi lineage dynamics elucidate the processes underlying the range expansion and demonstrate that migration into, and selection within, newly colonized sites operate on different time scales.

Borrelia burgdorferi strain and host sex influence pathogen prevalence and abundance in the tissues of a laboratory rodent host - Christopher B. Zinck; Prasobh Raveendran Thampy; Ryan O. M. Rego; Dustin Brisson; Nicholas H. Ogden; Maarten Voordouw (Molecular Ecology, 2022)
Experimental infections with different pathogen strains give insight into pathogen life history traits. The purpose of the present study was to compare variation in tissue infection prevalence and spirochete abundance among strains of Borrelia burgdorferi in a rodent host ( Mus musculus , C3H/HeJ). Male and female mice were experimentally infected via tick bite with one of 12 strains. Ear tissue biopsies were taken at days 29, 59 and 89 postinfection, and seven tissues were collected at necropsy. The presence and abundance of spirochetes in the mouse tissues were measured by quantitative polymerase chain reaction. To determine the frequencies of our strains in nature, their multilocus sequence types were matched to published data sets. For the infected mice, 56.6% of the tissues were infected with B. burgdorferi . The mean spirochete load in the mouse necropsy tissues varied 4.8‐fold between the strains. The mean spirochete load in the ear tissue biopsies decreased rapidly over time for some strains. The percentage of infected tissues in male mice (65.4%) was significantly higher compared to female mice (50.5%). The mean spirochete load in the seven tissues was 1.5× higher in male mice compared to female mice; this male bias was 15.3× higher in the ventral skin. Across the 11 strains, the mean spirochete loads in the infected mouse tissues were positively correlated with the strain‐specific frequencies in their tick vector populations. The study suggests that laboratory‐based estimates of pathogen abundance in host tissues can predict the strain composition of this important tick‐borne pathogen in nature.

The role of host phenology for parasite transmission - Hannelore MacDonald; Erol Akçay; Dustin Brisson (Theoretical Ecology, 2021)
Phenology is a fundamental determinant of species distributions, abundances, and interactions. In host–parasite interactions, host phenology can affect parasite fitness due to the temporal constraints it imposes on host contact rates. However, it remains unclear how parasite transmission is shaped by the wide range of phenological patterns observed in nature. We develop a mathematical model of the Lyme disease system to study the consequences of differential tick developmental-stage phenology for the transmission of B. burgdorferi . Incorporating seasonal tick activity can increase B. burgdorferi fitness compared to continuous tick activity but can also prevent transmission completely. B. burgdorferi fitness is greatest when the activity period of the infectious nymphal stage slightly precedes the larval activity period. Surprisingly, B. burgdorferi is eradicated if the larval activity period begins long after the end of nymphal activity due to a feedback with mouse population dynamics. These results highlight the importance of phenology, a common driver of species interactions, for the fitness of a parasite.

Population structure of the C hagas disease vector, T riatoma infestans, at the urban–rural interface - Erica A. Foley; Camilo E. Khatchikian; Josephine Hwang; Jenny Ancca‐Juárez; Katty Borrini‐Mayori; Victor R. Quıspe‐Machaca; Michael Z. Levy; Dustin Brisson (Molecular Ecology, 2013)
The increasing rate of biological invasions resulting from human transport or human‐mediated changes to the environment has had devastating ecological and public health consequences. The kissing bug, T riatoma infestans , has dispersed through the P eruvian city of A requipa. The biological invasion of this insect has resulted in a public health crisis, putting thousands of residents of this city at risk of infection by T rypanosoma cruzi and subsequent development of C hagas disease. Here, we show that populations of T ria. infestans in geographically distinct districts within and around this urban centre share a common recent evolutionary history although current gene flow is restricted even between proximal sites. The population structure among the T ria. infestans in different districts is not correlated with the geographical distance between districts. These data suggest that migration among the districts is mediated by factors beyond the short‐range migratory capabilities of T ria. infestans and that human movement has played a significant role in the structuring of the T ria. infestans population in the region. Rapid urbanization across southern S outh A merica will continue to create suitable environments for T ria. infestans, and knowledge of its urban dispersal patterns may play a fundamental role in mitigating human disease risk.